Unsteady Aerodynamic Design of a Flapping Wing Combined with a Bionic Wavy Leading Edge - Xuan Bai; Hao Zhan; Baigang Mi (Applied Sciences, 2023)
Based on the bionic design of the humpback whale fin, a passive flow control method is proposed to obtain greater flapping lift by applying the wavy leading edge structure to the straight symmetrical flapping wing. The leading edge of the conventional flapping wing is replaced by the wavy shape represented by regular trigonometric function to form a special passive flow control configuration imitating the leading edge of the humpback whale fin. The dynamic aerodynamic performance and flow field characteristics of straight wing and wavy leading edge flapping wing with different parameters are compared and analyzed by CFD numerical simulation. The simulation results show that the wavy leading edge structure changes the flow field of the baseline flapping wing and reduces the pressure on the upper surface of the flapping wing during the process of downward flapping, thereby increasing the pressure difference between the upper and lower surfaces of the flapping wing and increasing the lift. The sensitivity analysis of the design parameters shows that in order to obtain the maximum lift coefficient while losing the least thrust, the smaller amplitude should be selected on the premise of selecting the smaller wavelength. Among the configurations of different design parameters calculated in this paper, the optimal wavy leading edge flapping wing configuration increases the time average lift coefficient by 32.86% and decreases the time average thrust coefficient by 14.28%. Compared with the straight wing, it has better low-speed flight and can withstand greater take-off weight.